Dorado. Art and beauty in the urban periphery (REVISTA NODO, 2021)
This article presents some of the theoretical and methodological elements that were part of the Dorado research-creation, carried out within the Faculty of Arts of the Antonio Nariño University, whose fundamental purpose was the discovery and reassessment of these other aesthetics that can be seen in the Ciudad Bolívar (Bogota, Colombia) locality to break with the negative stereotype that is had of it and that is still present in the collective imagination of a large part of the Bogota population. The product of this process is the Dorado work, composed of 15 photographs printed on canvas and intervened with golden acrylic paint and a series of cartographies that give an account of the experiences gathered in each route carried out, which is succinctly shown in this communication. All this to value the aesthetic, spatial and human riches of a peripheral sector whose journey is marked by daily struggles for the dignity of existence in all senses.
Keywords: Culture; Art; Visual arts; Urban area; Social exclusion